Total Synthesis of Ascospiroketal B - Hara, Yoshiyori; Kamaike, Kazuo; Ota, Koichiro; Miyaoka, Hiroaki (Synlett, 2020)
An enantioselective total synthesis of the marine tricyclic polyketide ascospiroketal B, previously isolated from the marine-derived fungus Ascochyta salicorniae, was accomplished in 21 steps by using an improved route. The intriguing 5,5-spiroketal-cis-fused-γ-lactone core was constructed through rearrangement of an epoxide, in conjunction with an acid-mediated spiroketalization.
Keywords: ascospiroketal B; polyketides; spiroketals; rearrangement; total synthesis